Changes in the functional state of the endothelium in conditions of experimental rhegmatogenous retinal detachment and its correction - Levytskyi, I. M.; Savytskyi, I. V.; Levytska, G. V.; Miastkivska, I. V. (Journal of Education, Health and Sport, 2017)
RRD – photoreceptors detachment from retinal pigment epithelial by retrovitreal fluid, which penetrates through the breakdown of the neurosensory part. Purpose: investigation of endothelial dysfunction in rhegmatogenous retinal detachment pathogenesis and analysis of correction methods effectiveness.Von Willebrand factor (VWF) is common marker of endothelial dysfunction. It was established increase in its level in the 7th day of the research in all groups in which rats were modeled rhegmatogenous retinal detachment. Differences in the comparison of these groups among themselves have not been identified.At 14th day, it is observed endothelial dysfunction development in group 2 (differences in comparison with the data of intact animals already at the level of significance p <0.01). In group of rats receiving a two-component correction, decrease in the level of VWF was found. In the group receiving the three-component correction, the level of the von Willebrand factor is more strongly approximated to the norm (p <0.05 when comparing the data of this group and the animals that did not undergo correction of the experimental RRD)On 21st day no differences were found when comparing the results of intact animals with the data of each group receiving correction of the modeled RRD, indicating the normalization of endothelial cells functioning. It is worth noting that in the group in which animals received cytokoline, D-asparagine and L-arginine (group №4), most expressed normalized functional state of the endothelium, as evidenced by the differences in comparison with the data of 2nd and 3rd groups on levels of significance p <0.01